Association of the clinicopathological characteristics and proteinuria remission of pediatric IgAV with nephrotic-range proteinuria: A retrospective cohort study - Kang, Zhijuan; Xun, Mai; Li, Zhihui; Yang, Zuocheng (Frontiers in Pediatrics, 2022)
Background: IgAV (IgA vasculitis) combined with nephrotic-range proteinuria is uncommon, and nephrotic-range proteinuria is considered a risk factor for poor prognosis in children with IgAV. There are few clinical studies with large samples. Methods: Children with IgAV and nephrotic-range proteinuria who were hospitalized in the Department of Nephrology, Rheumatology and Immunology, Hunan Children's Hospital from March 2008 to January 2020 were retrospectively studied; they were aged ≤ 18 years and were followed up for ≥12 months. We analyzed the clinical characteristics, pathological changes, treatment responses and their relationships in patients with IgAV combined with nephrotic-range proteinuria. Results: Two hundred seventy-seven children were enrolled with an average age at onset of IgAV with nephritis (IgAVN) of 8.0 years (IQR, 6.0-10.0), of which 65.7% were aged 6~10 years. The male-to-female ratio was 1.35:1. All children had both nephrotic-range proteinuria and hematuria, 49 (17.7%) had hypoalbuminemia, and 9 (3.2%) had an eGFR <90 (mL/min/1.73 m2). All included children were followed up for at least one year. At 3, 6, and 12 months of follow-up, the remission rates of proteinuria in children with IgAV combined with nephrotic-range proteinuria were 27.8%, 62.1%, and 83.0%, respectively, and the remission rates of hematuria were 1.4%, 8.7%, and 35.7%, respectively. In addition, children with an age at onset of IgAV with nephrotic-range proteinuria ≥ 10 years, who were female, who had proteinuria ≥ 100 mg/kg/24 h and who had a pathological grade III or above had lower remission rates of hematuria and proteinuria (P<0.05).The multivariate factor analysis was performed by logistic regression showed that an age at onset of IgAVN ≥ 10 years and crescents were the risk factor for non-remission of proteinuria in the regression analysis at 12 months of follow-up (P<0.05). Conclusions:The age at onset of IgAVN, gender, proteinuria level, pathological grade and crescents significantly affected the remission of proteinuria in children with IgAV combined with nephrotic-range proteinuria.